Economic Value Added (Eva) Analysis to Measure Financial Performance in The Pharmaceutical Industry Listed on The Indonesia Stock Exchange (2018-2022 Period) - Sayyed Muhammad Fikri Assagaf; Anwar; Andi Mustika Amin; Anwar Ramli; Hety Budiyanti (International Humanity Advance, Business & Sciences, 2023)
Abstract This study aims to determine the financial performance of the pharmaceutical industry listed on the Indonesia Stock Exchange using the Economic Value Added (EVA) method during the 2018-2022 period. The type of research used is quantitative using descriptive data. The population in this study is the financial statements of the pharmaceutical industry listed on the Indonesia Stock Exchange consisting of PT Sido Muncul Tbk, PT Pyridam Farma Tbk, PT Kalbe Farma Tbk, PT Kimia Farma Tbk, PT Indofarma Tbk and PT Darya-Varia for the last 5 years, 2018-2022. The sample of this study is the statement of financial position and comprehensive income. The data collection technique used is documentation. The data analysis technique used is Economic Value Added (EVA) analysis which consists of NOPAT, Invested Capital, WACC, and Capital Charges. The results of this study indicate that the value of Economic Value Added (EVA) at PT Sido Muncul Tbk, PT Kalbe Farma Tbk, and PT Darya-Varia Laboratoria Tbk during the 2018-2022 period was always positive (EVA > 0) so it can be said that management is able to create added economic value for the company. However, PT Pyridam Farma Tbk in the period 2018 to 2022 cannot be fully said to be good because there is a negative EVA. In 2019 it was noted that the Economic Value Added (EVA) value of PT Pyridam Farma Tbk decreased to a negative value (EVA <0), so it can be said that the company has not been able to create added economic value for the company.